2021
DOI: 10.1002/ejoc.202100858
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Thiocarbamates

Abstract: An efficient isocyanide‐based synthesis of S‐thiocarbamates was discovered and thoroughly investigated. The new reaction protocol is a one‐pot procedure and allows the direct conversion of N‐formamides into thiocarbamates by initial dehydration with p‐toluene sulfonyl chloride to the respective isocyanide and subsequent addition of a sulfoxide component. Contrary to recent literature, which also uses isocyanides as starting material, but with other sulfur reagents than sulfoxides, in this protocol, no isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
3
3
0
Order By: Relevance
“…The lower T d,5% is expected to result from the cleavage of the thiocarbamate moiety, which is indicated by the two-step thermal degradation process (Figure S56–S60). In earlier studies, similar behavior was reported for polymers containing thiocarbamate moieties in the side chain, and a thermal decomposition to the corresponding thiol and isocyanate was verified via IR spectroscopy and gas chromatography coupled with mass spectrometry . Comparable degradation temperatures of thiocarbamate moieties between 219–228 °C were observed in this study, which further indicates the thiocarbamate cleavage of O -cellulose thiocarbamates in a first step.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The lower T d,5% is expected to result from the cleavage of the thiocarbamate moiety, which is indicated by the two-step thermal degradation process (Figure S56–S60). In earlier studies, similar behavior was reported for polymers containing thiocarbamate moieties in the side chain, and a thermal decomposition to the corresponding thiol and isocyanate was verified via IR spectroscopy and gas chromatography coupled with mass spectrometry . Comparable degradation temperatures of thiocarbamate moieties between 219–228 °C were observed in this study, which further indicates the thiocarbamate cleavage of O -cellulose thiocarbamates in a first step.…”
Section: Resultssupporting
confidence: 86%
“…In earlier studies, similar behavior was reported for polymers containing thiocarbamate moieties in the side chain, and a thermal decomposition to the corresponding thiol and isocyanate was verified via IR spectroscopy and gas chromatography coupled with mass spectrometry. 56 Comparable degradation temperatures of thiocarbamate moieties between 219−228 °C were observed in this study, which further indicates the thiocarbamate cleavage of O-cellulose thiocarbamates in a first step. DSC measurements revealed no observable glass transition in the range from −50 to 200 °C (Figure S61).…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…In all of these cases, a two-step degradation mechanism was observed, leading to the assumption that the thionocarbamate functional group starts degrading in these temperature ranges, followed by a second degradation step of the residual material. Similar behavior was also observed for S -thiocarbamate (thiolourethane)-containing polymers, where the degradation of the S -thiocarbamate functionality to the corresponding isocyanate and thiol could be detected …”
Section: Resultssupporting
confidence: 74%
“…Similar behavior was also observed for S-thiocarbamate (thiolourethane)-containing polymers, where the degradation of the S-thiocarbamate functionality to the corresponding isocyanate and thiol could be detected. 60 The second degradation step was evaluated at T d,50% , and a narrow temperature range was found for all materials (370− 388 °C), especially comparing the thionourethane with the oxourethane thermoset materials (Table 2). Similar degradation temperatures for castor oil/isophorone diisocyanate-based oxourethane prepolymers were also reported previously by Gurunathan et al with T d,50% = 382.9−431.0 °C, depending on the chosen polyol/diisocyanate ratio.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Blencowe et al , used a di­(thiocarbamate) that is almost identical to our recovered di­(thiocarbamate) to obtain masked isocyanate for PU synthesis, which is a safer synthesis route that is free of the use of toxic phosgene as a precursor. Moreover, our recovered di­(thiocarbamate) is O -organyl thiocarbamate, which can be easily converted into S -organyl thiocarbamate by a simple one-step reaction (see Figure S14). S -organyl thiocarbamates are important compounds mainly used in agriculture as insecticides, herbicides, etc .…”
Section: Results and Discussionmentioning
confidence: 99%